Rasch Model Measurement as Tools in Assessment for Learning - Sumintono, B. (2017)
Assessment for learning means to provide good information for teachers to help students learning better. Besides tools from the Classical Test Theory (CTT) approach that usually used by teacher, other approach which is called as objective measurement that based on probability is an alternative that can give more precise measurement. Rasch model provide psychometrics analysis techniques can be used by teachers to develop test items as well as an essential tools that can provide relevant information regard to students assessment for learning.